Effect of Roux-en-Y Bariatric Surgery on Lipoproteins, Insulin Resistance, and Systemic and Vascular Inflammation in Obesity and Diabetes - Yadav, Rahul; Hama, Salam; Liu, Yifen; Siahmansur, Tarza; Schofield, Jonathan; Syed, Akheel A.; France, Michael; Pemberton, Philip; Adam, Safwaan; Ho, Jan Hoong; Aghamohammadzadeh, Reza; Dhage, Shaishav; et al. (Frontiers in Immunology, 2017)
Purpose: Obesity is a major modifiable risk factor for cardiovascular disease. Bariatric surgery is considered to be the most effective treatment option for weight reduction in obese patients with and without type 2 diabetes. Objective: To evaluate changes in lipoproteins, insulin resistance, mediators of systemic and vascular inflammation and endothelial dysfunction following Roux-en-Y bariatric surgery in obese patients with and without diabetes. Materials and methods: Lipoproteins, insulin resistance, mediators of systemic and vascular inflammation, and endothelial dysfunction were measured in 37 obese patients with (n=17) and without (n=20) type 2 diabetes, before and six and twelve months after Roux-en-Y bariatric surgery. Two way between subject ANOVA was carried out to study the interaction between independent variables (time since surgery and presence of diabetes) and all dependent variables Results: There was a significant effect of time since surgery on (large effect size) weight, BMI, waist circumference, TG, sdLDL ApoB, HOMA-IR, CRP, MCP-1, ICAM-1, E selectin, P selectin, leptin and adiponectin. BMI and waist circumference had the largest impact of time since surgery. The effect of time since surgery was noticed mostly in the first 6 months. Absence of diabetes led to a significantly greater reduction in TC, LDL-C and nonHDL-C although the effect size was small to medium. There was a greater reduction in TG and HOMA-IR in patients with diabetes with a small effect size. No patients were lost to follow up. Conclusion: Lipoproteins, insulin resistance, mediators of systemic and vascular inflammation, and endothelial dysfunction improve mostly 6 months after bariatric surgery in obese patients with and without diabetes. ClinicalTrials.gov Identifier: NCT02169518 https://clinicaltrials.gov/ct2/show/NCT02169518?term=paraoxonase&cntry1=EU%3AGB&rank=1